2007
DOI: 10.1108/13555850710720911
|View full text |Cite
|
Sign up to set email alerts
|

The effects of single‐message single‐source mixed word‐of‐mouth on product attitude and purchase intention

Abstract: Purpose -This study seeks to investigate how attitude towards and purchase intention of a product will be affected by involvement level and presentation order of positive and negative word-of-mouth (WOM) information when presented in a single-message single-source context. Design/methodology/approach -Two studies were conducted with undergraduates of a top Asian university with sample sizes of 221 and 253 using experimental setups. Findings -It was found that subjects tend to base their evaluations more on lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(10 citation statements)
references
References 16 publications
1
8
0
1
Order By: Relevance
“…Lai Ying and Chung (2007) showed that unlike adverse WOM, positive WOM led to a customer’s higher intention to buy a particular good or service. Gruen et al (2006) pondered over digital information platforms and ascertained that digital WOM affected not only the customers’ presumed value of a firm’s goods but also their loyalty.…”
Section: Results Conclusion and Future Researchmentioning
confidence: 99%
“…Lai Ying and Chung (2007) showed that unlike adverse WOM, positive WOM led to a customer’s higher intention to buy a particular good or service. Gruen et al (2006) pondered over digital information platforms and ascertained that digital WOM affected not only the customers’ presumed value of a firm’s goods but also their loyalty.…”
Section: Results Conclusion and Future Researchmentioning
confidence: 99%
“…A significant amount of academic research has referred to WOM as one of the most influential factors in the business (Duan et al, 2008;Tam and Khuong, 2016). Ying and Chung (2007) suggest that WOM can help to improve or harm marketing of products.…”
Section: Wommentioning
confidence: 99%
“…Moreover, the product information through e-WOM from a reliable person will make the receiver feel more trustworthy even the receiver has not yet used the product (Kavoura & Stavrianeas, 2015). Ying and Chung (2007) indicated that positive e-WOM stimulated a positive attitude and influenced purchasing intention. Furthermore, a positive message of e-WOM from reliable reference sources leads to a better attitude toward a brand than those of unreliable sources (Wu & Wang, 2011).…”
Section: H1bmentioning
confidence: 99%